2005
DOI: 10.1634/theoncologist.10-3-183
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Oral Rubitecan in Previously Treated Pancreatic Cancer Patients

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…One co-operative group trial reported that only 45% of patients with APC went on to receive additional therapy following progression on front-line study treatment (Schrag et al , 2007). A number of small prospective single-arm studies have evaluated both cytotoxic and/or targeted agents in the setting of gemcitabine-refractory disease, generally demonstrating low response rates and progression-free survival of a few months at best (Burris et al , 2005; Boeck et al , 2007; Kulke et al , 2007; Ko et al , 2008, 2010; Oh et al , 2010; O'Reilly et al , 2010). Results from a randomised German trial for the second-line treatment of APC (CONKO-003) suggested a weekly regimen called OFF (oxaliplatin, 5-FU given as a 24-hour infusion, and folinic acid) may improve patient outcomes in patients refractory to gemcitabine (Pelzer et al , 2008, 2011).…”
mentioning
confidence: 99%
“…Salvage treatment with a single agent, like pemetrexed [32], rubitecan [33], raltitrexed [34], epirubicin [35], capecitabine [36], docetaxel [37] and paclitaxel [38], yielded a median survival of 3.5–4.6 months and a 1-year OS of 0–15%. Apparently better results were reported with combination chemotherapy at time of salvage, with median survival times ranging between 5.2 and 8.3 months and 1-year OS between 12 and 32% [6,7,26,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%